Design, synthesis, pharmacological characterization of a fluorescent agonist of the P2Y14 receptor. Issue 21 (1st November 2015) - Kiselev, Evgeny; Balasubramanian, Ramachandran; Uliassi, Elisa; Brown, Kyle A.; Trujillo, Kevin; Katritch, Vsevolod; Hammes, Eva; Stevens, Raymond C.; Harden, T. Kendall; Jacobson, Kenneth A.
Graphical abstract: Abstract: The P2Y14 R is a Gi/o -coupled receptor of the P2Y family of purinergic receptors that is activated by extracellular UDP and UDP-glucose (UDPG). In an earlier report we described a P2Y14 R fluorescent probe, MRS4174, based on the potent and selective antagonist PPTN, a naphthoic acid derivative. Here, we report the design, preparation, and activity of an agonist-based fluorescent probe MRS4183 (11 ) and a shorter P2Y14 R agonist congener, which contain a UDP-glucuronic acid pharmacophore and BODIPY fluorophores conjugated through diaminoalkyl linkers. The design relied on both docking in a P2Y14 R homology model and established structure activity relationship (SAR) of nucleotide analogs.11 retained P2Y14 R potency with EC50 value of 0.96 nM (inhibition of adenylyl cyclase), compared to parent UDPG (EC50 47 nM) and served as a tracer for microscopy and flow cytometry, displaying minimal nonspecific binding. Binding saturation analysis gave an apparent binding constant for11 in whole cells of 21.4 ± 1.1 nM, with a t 1/2 of association at 50 nM11 of 23.9 min. Known P2Y14 R agonists and PPTN inhibited cell binding of11 with the expected rank order of potency. The success in the identification of a new P2Y14 R fluorescent agonist with low nonspecific binding illustrates the advantages of rational design based on recently determined GPCR X-ray structures. Such conjugates will be useful tools in expanding the SAR of this receptor, which still lacks chemical diversity in its collective ligands.